Boundedness and Hölder continuity of weak solutions of the nonlinear boundary-value problem for elliptic equations with general nonstandard growth conditions - Gumpyong Ri; Dukman Ri (Mathematica Bohemica)
We study a nonlinear boundary-value problem for elliptic equations with critical growth conditions involving Lebesgue measurable functions. We prove global boundedness and Hölder continuity of weak solutions for this problem. Our results generalize the ones obtained by P. Winkert and his colleagues (2012) not only in the variable exponent case but also in the constant exponent case.